1976
DOI: 10.1159/000144563
|View full text |Cite
|
Sign up to set email alerts
|

Stature estimation from femur and humerus by regression and autometry

Abstract: Estimation of stature from a single extremity bone is a common forensic practice and many regression equations are given by various workers. In India, Pearson’s formula is the most commonly used method to determine the height. These regression equations were subjected to verification on 194 (97 pairs) femora and 102 (51 pairs) humeri from India. It was seen that the Pearsonian formulae did not give exact results. The regression formulae differed statistically in both sexes in femur and humerus. These are calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Kate and Muzumdar [28] after comparing the derived regression equation for Maharashtrian and Punjabis with that of Pearson's regression formula derived from English bone stated that Pearson's regression equation does not give exact results in Indian population. Similar view by Kaore et al [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kate and Muzumdar [28] after comparing the derived regression equation for Maharashtrian and Punjabis with that of Pearson's regression formula derived from English bone stated that Pearson's regression equation does not give exact results in Indian population. Similar view by Kaore et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the regression formula derived by Allbrook [7] for estimating the stature in the British population is not suitable to estimate the stature in Indian population. [16,28] As individuals stop growing in height on completion of the union of the epiphysis and the diaphysis, which is usually by the age of 18 to 20 years, therefore all the individuals considered for the purpose of the study were either at or above the age of 20years. In this study, the mean height for male was 164.5±8.257cm and for female was 155.3±5.854cm; and the mean PCTL for male was 38.24±2.343cm which was significantly (p<0.0001) greater than the female which was 36.064±2.464cm.…”
Section: Discussionmentioning
confidence: 99%
“…However in their absence, estimation of living stature can also be done from the long bones of the upper limb viz. Humerus, radius & ulna (Celbis & Agritmis, 2006;Kate & Majumdar, 1976). For this purpose, either humerus can be used alone (Steele & Mckern, 1969) or collectively with other bones of upper limbs (Mall et al, 2001), for the determination of sex and the estimation of stature of an individual.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of height by using one bone of the extremity is a frequent forensic activity and many estimation formulas have been produced by the researchers (Kate et al, 1976). Narde et al, 2013 study on estimation of height based on length and width of foot in population Nagpur, India with average height 156,28 cm yield formula of TB (P) = 53,0 + 4,26 * long palm Right foot ± 0.992 cm with correlation coefficient (r) = 0.9869.…”
Section: Introductionmentioning
confidence: 99%